THE MAIN TYPES OF HUMAN ACTIVITY AND INFLUENCE ON THE HUMAN ORGANISM - Shermatova Yakutkhan Sabirovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article is about the main types of human activity, the impact of this activity on human health. It will be explained about the means of influencing the body of the factors that have a negative effect on the person.